Writing Anxiety and Facebook-mediated Feedback - Yufrizal, Hery; Sutarsyah, Cucu; Sudirman, (Advances in Social Sciences Research Journal, 2020)
Feedback can be classified into two common types, namely teacher and peer feedback. Teacher feedback is feedback provided by teachers and peer feedback is feedback provided by other students. The aim of this article is to explore writing feedback provided by students and its impact to the quality of writing by students who reeceive the feedback. The research was undertaken to higher education students enrolled in wtiting class. The result showed that writing in foreign language makes the students experience different dimensions of writing anxiety, such as somatic anxiety, avoidance behavior, and cognitive anxiety.